Mobilisation of savings in small states : the Commonwealth Caribbean - Thomas, Clive Y. (Univ. of Guyana. Institute of Development Studies GeorgetownGY)
Deals with issues centering on the mobilization of private domestic voluntary savings in the Commonwealth Caribbean. Identifies the major theoretical issues and surveys recent data on savings trends and patterns in the region. Addresses policy issues drawn from the theoretical and survey analysis.